PENGARUH MEDIA SOSIAL TERHADAP MOTIVASI BEROLAHRAGA PADA MAHASISWA UNIVERSITAS NEGERI MEDAN (UNIMED) SUMATERA UTARA - Prakas Purba, Charles; Amelia, Lisa; Pandapotan Sitompul, Andriano; Rivaldo Gulo, Frans; Indra Siregar, Yan; Arima, Putra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Advances in Information and Communication Technology (ICT) in the digital era have integrated social media into students' daily routines, including their fitness behavior. This study aims to examine the real influence of social media on the exercise motivation of active students at the State University of Medan (UNIMED) while evaluating the positive and negative impacts of these digital interactions. Using a quantitative approach with a correlational survey method, a structured Likert-scale questionnaire was distributed via Google Form to 30 students selected by purposive sampling. Data analysis was performed using descriptive statistics and simple linear regression in SPSS 26. The results showed that the level of social media usage was relatively high (mean = 76.4) and students' exercise motivation was also strong (mean = 73.8). The regression model (Y = 21.340 + 0.687X) proved a positive and significant influence (thitung = 6.134, p < 0.05), where social media contributed to explaining the variance in motivation by 56.8%. Positive impacts include increased awareness of healthy living and insight into exercise techniques through platforms such as TikTok and Instagram. Conversely, negative impacts include body image disturbances, motivation for social approval, and even device addiction. The conclusion of this study is that social media significantly influences exercise motivation, necessitating wise and balanced use.